High-strength cobalt-chromium-based alloy for a puncture needle and a method for manufacturing the same
Patent Information
- Application Number
- CN202410004722.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-02
- Publication Date
- 2026-10-23
- Estimated Expiration
- 2044-01-02
AI Technical Summary
硬度过高可能导致穿刺困难,增加对患者组织的损伤;硬度过低则可能导致针头已发生变形,影响使用效果
Smart Images

Figure CN117821827B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of cobalt-chromium based alloy materials and relates to the preparation of a cobalt-nickel based biomaterial with high strength, moderate hardness, resistance to deformation, and good biocompatibility. Technical Background
[0002] Metallic materials have a wide range of applications in the biomedical field, such as medical instruments, surgical instruments, and implant materials. Clinically used metallic implant materials mainly include medical precious metals, stainless steel, cobalt-based alloys, titanium alloys, and nickel-titanium shape memory alloys. Co-Cr-based alloys exhibit excellent corrosion resistance, fatigue resistance, and wear resistance, possessing good comprehensive mechanical properties, making them a commonly used biomedical material. For joints experiencing frictional activity, cobalt-chromium alloy artificial joints are generally used. There is a significant demand for needles in diagnostic and drug injection procedures. A puncture needle is a medical device used to collect biological tissues, fluids, or perform interventional treatments. Its working principle involves inserting the needle tip into a specific location inside the patient's body through cutting or puncturing action to facilitate collection or treatment. Puncture needles are very common medical devices widely used in various medical fields, such as tumor treatment, radiology, and endoscopy.
[0003] During puncture, doctors need to precisely control the depth and direction of the needle to avoid damaging surrounding vital tissues or organs. Therefore, the needle material must meet the following requirements: high strength, good corrosion resistance, good biocompatibility, and moderate hardness. High strength ensures that the needle will not deform or break under pressure or friction during use. Furthermore, the hardness of the needle has a significant impact on its puncture performance and the extent of damage. Excessive hardness may lead to difficulty in puncture and increase damage to patient tissues; insufficient hardness may cause the needle to deform, affecting the effectiveness of the procedure. Summary of the Invention
[0004] This invention aims to provide a high-strength cobalt-chromium-based alloy for puncture needles and its preparation method. Based on Co, Cr, Fe, Ni, Mo, Mn, and Si, this alloy achieves a significant increase in strength while maintaining sufficient hardness through hot deformation, solution treatment, cold deformation, and aging treatment, thus meeting the performance requirements of puncture needles. To achieve the above objective, the technical solution provided by this invention is as follows:
[0005] The raw materials used in the cobalt-chromium-based alloy have the following mass percentages: Co 39-41%, Cr 19-21%, Fe 14-16%, Ni 14-15%, Mo 6-8%, Mn 1.5-2.5%, and Si 1-1.2%. After preparation, the alloy undergoes vacuum induction melting and homogenization annealing; hot extrusion yields a tube blank, followed by solution treatment and cold drawing to obtain a cobalt-chromium-based alloy tube blank; finally, aging treatment is performed to obtain a puncture needle with high strength and sufficient hardness. The homogenization process conditions are: holding at 1420–1460℃ for 12–24 h; the solution treatment conditions are: holding at 1100–1160℃ for 1–1.5 h, followed by rapid water cooling to room temperature; the cold drawing forming process involves a total deformation of 56–64% across multiple drawing passes; the aging treatment conditions are: holding at 600–650℃ for 1–1.5 h, followed by rapid water cooling to room temperature. After the above solution treatment, cold drawing forming, and aging treatment, the prepared cobalt-chromium-based alloy has an FCC structure in its matrix, with tens of nanometer-sized manganese-rich precipitates within the grains. These precipitates have an HCP structure; the tens of nanometer-sized manganese-rich HCP precipitates are distributed within the twins and the matrix, coexisting with a large number of dislocations and nanotwins. The unique microstructure resulting from the coupling of nanotwins, dislocations, and nanoprecipitates gives the alloy extremely high strength. The tensile strength of the puncture needle blank is higher than 1900 MPa, and the hardness is higher than 670 HV. The puncture needle can be prepared by subsequent machining and polishing.
[0006] The method for preparing a high-strength cobalt-chromium-based alloy for puncture needles with high strength and sufficient hardness includes the following steps:
[0007] (1) Raw material preparation: Prepare Co, Cr, Fe, Ni, Mo, Mn and Si raw materials according to the required proportions. You can also use intermediate alloys such as NiCo, NiCr and FeSi with known compositions.
[0008] (2) Vacuum induction melting: After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 1.33 × 10⁻⁶. -3 ~1.33×10 -4 Maintain the pressure at 0.04 MPa for 2–2.5 hours. After turning off the vacuum pump, purge with 0.04 MPa high-purity argon gas as a protective atmosphere. Then, slowly raise the temperature to 1600–1650 °C using a high-frequency induction coil. Once the block has melted, pour it into a casting mold to obtain the casting billet.
[0009] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1420-1460℃, and kept at the temperature for 12-24 hours to obtain a homogenized billet.
[0010] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The temperature is heated to 1060-1180℃ before hot extrusion; the hot extrusion ratio is 8-20. Hot extruded tube blanks are obtained after hot extrusion.
[0011] (5) Solution treatment: The hot extruded tube blank is loaded into a heat treatment furnace and heated to 1100-1160°C under vacuum or argon protection, held for 1-1.5 hours, and then rapidly cooled to room temperature to obtain the solution-treated tube blank.
[0012] (6) Cold drawing forming. The tube is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 56-64% to obtain a cold-drawn tube blank. When the size of the cold-drawn tube blank is larger than the size of the puncture needle, steps (5) and (6) can be repeated until the size of the cold-drawn tube blank meets the size requirements of the puncture needle to obtain a cold-drawn tube for the puncture needle.
[0013] (7) Aging treatment: The cold-drawn tube blank is heated to 600-650℃ and held for 1-1.5h, and then rapidly cooled to room temperature to obtain the aged tube blank.
[0014] In the above process, the dimensions of the cast billet should meet the requirements of the hot extrusion process. After homogenization, the billet can be machined by turning and boring to produce a billet that meets the size and shape requirements of the hot extrusion process. After cold drawing, the dimensions of the tube blank should meet the size requirements of the puncture needle. When the size of the cold-drawn tube blank is larger than the size of the puncture needle, repeated solution treatment can be performed; that is, multiple solution treatment-cold drawing cycles can be performed to finally obtain a puncture needle that meets the size requirements.
[0015] After the above-mentioned solution treatment, cold drawing, and aging treatment, the prepared cobalt-chromium-based alloy has an FCC structure in its matrix, with tens of nanometer-sized manganese-rich precipitates within the grains. These precipitates have an HCP structure. The tens of nanometer-sized manganese-rich HCP precipitates are distributed within the twins and the matrix, coexisting with a large number of dislocations and nanotwins. The special microstructure resulting from the coupling of nanotwins, dislocations, and nanoprecipitates gives the alloy extremely high strength. The puncture needle blank has extremely high tensile strength, exceeding 1900 MPa, and a hardness exceeding 670 HV. The puncture needle can then be fabricated through machining and polishing. Attached Figure Description
[0016] Figure 1 Stress-strain curves of cobalt-chromium based alloys in Example 1
[0017] Figure 2 XRD diffraction pattern of cobalt-chromium based alloy in Example 2
[0018] Figure 3 Metallographic photograph of the cross section in Example 3
[0019] Figure 4 TEM images of nanotwins and dislocations in Example 4
[0020] Figure 5 TEM image of the diffraction spots of the precipitated phase in Example 5 Detailed Implementation
[0021] Example 1
[0022] (1) Raw material preparation: Weigh out 39.3% Co, 19% Cr, 16% Fe, 15% Ni, 8% Mo, 1.5% Mn, and 1.2% Si according to the mass ratio;
[0023] (2) Vacuum induction melting. After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 1.33 × 10⁻⁶. -3 Maintain the pressure at 0.04 MPa for 2.5 hours. After turning off the vacuum pump, purge with 0.04 MPa high-purity argon gas as a protective atmosphere. Then, slowly raise the temperature to 1600℃ using a high-frequency induction coil. Once the block has melted, pour it into a casting mold to obtain the casting billet.
[0024] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1420℃, and kept at that temperature for 24 hours to obtain a homogenized billet.
[0025] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The billet is heated to 1060℃ before hot extrusion; the hot extrusion ratio is 8. After hot extrusion, hot extruded tube blanks are obtained.
[0026] (5) Solution treatment. The hot-extruded tube blank is loaded into a heat treatment furnace and heated to 1100°C under vacuum or argon protection. It is held for 1.5 hours and then rapidly cooled to room temperature to obtain the solution-treated tube blank.
[0027] (6) Cold drawing forming. The tube blank is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 56%.
[0028] (7) Aging treatment. The cold-drawn tube blank is heated to 600°C and held for 1.5 hours, and then rapidly cooled to room temperature to obtain the aged tube blank.
[0029] The matrix of the cobalt-chromium-based alloy prepared by the above method has an FCC structure, and the grains contain manganese-rich precipitates of tens of nanometers in size, which have an HCP structure. Figure 1The figure shows the stress-strain curve of the cobalt-chromium-based alloy in Example 1. This alloy exhibits extremely high tensile strength, reaching 1940 MPa. The prepared cobalt-chromium-based alloy has an FCC structure in its matrix, with tens of nanometer-sized manganese-rich precipitates within the grains. These precipitates have an HCP structure. The tens of nanometer-sized manganese-rich HCP precipitates are distributed within the twins and matrix, coexisting with a large number of dislocations and nanotwins. The unique microstructure resulting from the coupling of nanotwins, dislocations, and nanoprecipitates gives the alloy extremely high strength; the alloy has a strength of 1940 MPa and a hardness of 685 HV, making it suitable for manufacturing high-strength, small-diameter tubing and for the fabrication of puncture needles.
[0030] Example 2
[0031] (1) Raw material preparation: Weigh out 41% Co, 21% Cr, 14% Fe, 14% Ni, 6.5% Mo, 2.5% Mn, and 1% Si according to the mass ratio;
[0032] (2) Vacuum induction melting. After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 1.33 × 10⁻⁶. -4 Maintain the pressure at 0.04 MPa for 2 hours. After turning off the vacuum pump, purge with 0.04 MPa high-purity argon gas as a protective atmosphere. Then, slowly raise the temperature to 1650°C using a high-frequency induction coil. Once the block has melted, pour it into a casting mold to obtain the casting billet.
[0033] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1460℃, and held for 12 hours to obtain a homogenized billet.
[0034] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The billet is heated to 1180℃ before hot extrusion; the hot extrusion ratio is 20. After hot extrusion, hot extruded tube blanks are obtained.
[0035] (5) Solution treatment. The hot-extruded tube blank is placed in a heat treatment furnace and heated to 1160°C under vacuum or argon protection. It is held for 1 hour and then rapidly water-cooled to room temperature to obtain the tube blank after solution treatment.
[0036] (6) Cold drawing forming. The tube blank is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 64%.
[0037] (7) Aging treatment. The cold-drawn tube blank is heated to 650°C and held for 1 hour, and then rapidly cooled to room temperature to obtain the aged tube blank.
[0038] The cobalt-chromium-based alloy prepared by the above method has an FCC structure in its matrix, with manganese-rich precipitates of tens of nanometers in size within the grains. These precipitates have an HCP structure. This alloy exhibits extremely high tensile strength, reaching 1900 MPa. Figure 2 The XRD diffraction pattern of the cobalt-chromium-based alloy in Example 2 shows that the alloy matrix has an FCC structure. The grains contain manganese-rich precipitates of tens of nanometers in size, which have an HCP structure. These manganese-rich HCP precipitates are distributed within the twins and matrix, coexisting with numerous dislocations and nanotwins. This unique microstructure, with its coupling of nanotwins, dislocations, and nanoprecipitates, gives the alloy extremely high strength; the alloy has a strength of 1900 MPa and a hardness of 680 HV, making it suitable for manufacturing high-strength, small-diameter tubing, and ideal for puncture needle fabrication.
[0039] Example 3
[0040] (1) Raw material preparation: Weigh out 39% Co, 21% Cr, 16% Fe, 14.7% Ni, 6% Mo, 2.2% Mn, and 1.1% Si according to the mass ratio;
[0041] (2) Vacuum induction melting. After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 6.3 × 10⁻⁶. -4 The pressure was maintained at 0.04 MPa for 2.3 hours. After turning off the vacuum pump, 0.04 MPa of high-purity argon gas was introduced as a protective atmosphere. Then, a high-frequency induction coil was used to slowly raise the temperature to 1630°C. After the block melted, it was poured into a casting mold to obtain the casting billet.
[0042] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1450℃, and held for 16 hours to obtain a homogenized billet.
[0043] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The billet is heated to 1100℃ before hot extrusion; the hot extrusion ratio is 14. After hot extrusion, hot extruded tube blanks are obtained.
[0044] (5) Solution treatment. The hot-extruded tube blank is loaded into a heat treatment furnace and heated to 1120°C under vacuum or argon protection, held for 1.4 hours, and then rapidly water-cooled to room temperature to obtain the solution-treated tube blank.
[0045] (6) Cold drawing forming: The tube blank is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 60%.
[0046] (7) Aging treatment: The cold-drawn tube blank is heated to 620°C and held for 1.2 hours, and then rapidly cooled to room temperature to obtain the aged tube blank.
[0047] The cobalt-chromium-based alloy prepared by the above method has an FCC matrix with manganese-rich precipitates of tens of nanometers within the grains, exhibiting an HCP structure. This alloy possesses extremely high tensile strength, reaching 1928 MPa. The alloy matrix has an FCC structure. Figure 3 The cross-sectional metallographic photograph of Example 3 shows numerous broadened, elongated deformed grains in the alloy, with a large number of slip lines within the grains. Tens of nanometer-sized manganese-rich HCP precipitates are distributed within the twins and matrix, coexisting with a large number of dislocations and nanotwins. This unique microstructure, with the coupling of nanotwins, dislocations, and nanoprecipitates, gives the alloy extremely high strength; the alloy has a strength of 1928 MPa and a hardness of 682 HV, making it suitable for manufacturing high-strength, small-diameter tubing and for the fabrication of puncture needles.
[0048] Example 4
[0049] (1) Raw material preparation: Weigh out 40% Co, 20.6% Cr, 15.3% Fe, 14.1% Ni, 7% Mo, 2% Mn, and 1% Si according to the mass ratio;
[0050] (2) Vacuum induction melting: After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 4.2 × 10⁻⁶. -4 The pressure was maintained at 0.04 MPa for 2.3 hours. After turning off the vacuum pump, 0.04 MPa of high-purity argon gas was introduced as a protective atmosphere. Then, a high-frequency induction coil was used to slowly raise the temperature to 1620°C. After the block melted, it was poured into a casting mold to obtain the casting billet.
[0051] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1430℃, and held for 18 hours to obtain a homogenized billet.
[0052] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The billet is heated to 1120℃ before hot extrusion; the hot extrusion ratio is 12. After hot extrusion, hot extruded tube blanks are obtained.
[0053] (5) Solution treatment: The hot extruded tube blank is loaded into a heat treatment furnace and heated to 1135°C under vacuum or argon protection. It is held for 1.4 hours and then rapidly cooled to room temperature to obtain the tube blank after solution treatment.
[0054] (6) Cold drawing forming: The tube blank is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 62%.
[0055] (7) Aging treatment: The cold-drawn tube blank is heated to 620°C and held for 1.3 hours, and then rapidly cooled to room temperature to obtain the aged tube blank.
[0056] The cobalt-chromium-based alloy prepared by the above method has an FCC matrix with manganese-rich precipitates of tens of nanometers in size within the grains, exhibiting an HCP structure. This alloy possesses extremely high tensile strength, reaching 1917 MPa. The alloy matrix has an FCC structure. The alloy contains many broadened, elongated deformed grains, and numerous slip lines exist within the grains. Figure 4 The image shows TEM images of nanotwins and dislocations in Example 4. Manganese-rich HCP precipitates, ranging in size from tens of nanometers, are distributed within the twins and matrix, coexisting with numerous dislocations and nanotwins. This unique microstructure, characterized by the coupling of nanotwins, dislocations, and nanoprecipitates, results in an alloy with extremely high strength; the alloy exhibits a strength of 1917 MPa and a hardness of 679 HV, making it suitable for manufacturing high-strength, small-diameter tubing and for the fabrication of puncture needles.
[0057] Example 5
[0058] (1) Raw material preparation: Weigh out 40.2% Co, 19.2% Cr, 15.6% Fe, 14.8% Ni, 7.4% Mo, 1.7% Mn and 1.1% Si according to the mass ratio;
[0059] (2) Vacuum induction melting: After weighing, the raw materials are placed in an Al2O3 crucible and melted using an induction melting furnace. Before melting, the vacuum level is raised to 8.2 × 10⁻⁶. -4 Maintain the pressure at 0.04 MPa for 2.1 hours. After turning off the vacuum pump, purge with 0.04 MPa high-purity argon as a protective atmosphere. Then, slowly raise the temperature to 1620°C using a high-frequency induction coil. Once the block has melted, pour it into a casting mold to obtain the casting billet.
[0060] (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1450℃, and kept at that temperature for 15 hours to obtain a homogenized billet.
[0061] (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press. The billet is heated to 1080℃ before hot extrusion; the hot extrusion ratio is 10. After hot extrusion, hot extruded tube blanks are obtained.
[0062] (5) Solution treatment: The hot extruded tube blank is loaded into a heat treatment furnace and heated to 1130°C under vacuum or argon protection. It is held for 1.3 hours and then rapidly cooled to room temperature to obtain the tube blank after solution treatment.
[0063] (6) Cold drawing forming: The tube blank is cold drawn using a tube drawing machine. The total deformation of the multiple drawing passes is 62%.
[0064] (7) Aging treatment: The cold-drawn tube blank is heated to 640℃ and held for 1.2h, and then quickly cooled to room temperature to obtain the tube blank after aging treatment.
[0065] The cobalt-chromium-based alloy prepared by the above method has an FCC matrix with tens of nanometer-sized manganese-rich precipitates within the grains, exhibiting an HCP structure. This alloy possesses extremely high tensile strength, reaching 1934 MPa. The alloy matrix has an FCC structure. The alloy contains many broadened, elongated deformed grains, and numerous slip lines exist within the grains. Figure 5 This is a TEM image of the diffraction spots of the precipitated phase in Example 5. The manganese-rich HCP precipitates, at the tens of nanometer scale, are distributed within the twins and matrix, coexisting with numerous dislocations and nanotwins. This unique microstructure, with the coupling of nanotwins, dislocations, and nanoprecipitates, gives the alloy extremely high strength; the alloy has a strength of 1934 MPa and a hardness of 683 HV, making it suitable for manufacturing high-strength, small-diameter tubing and for the fabrication of puncture needles.
Claims
1. A high-strength cobalt-chromium-based alloy for puncture needles, characterized in that: The raw materials used in cobalt-chromium-based alloys have the following mass percentages: Co 39-41%, Cr 19-21%, Fe 14-16%, Ni 14-15%, Mo 6-8%, Mn 1.5-2.5%, and Si 1-1.2%. The preparation method of the high-strength cobalt-chromium-based alloy for the puncture needle includes: after preparation, vacuum induction melting and homogenization annealing treatment. Hot extrusion yields an extruded tube blank; the extruded tube blank undergoes solution treatment followed by cold drawing to obtain a cobalt-chromium-based alloy piercing needle tube blank; the solution treatment involves placing the hot-extruded tube blank into a heat treatment furnace, adding it to 1100~1160 ℃ under vacuum or argon protection, holding it at that temperature for 1~1.5 h, and then rapidly water-cooling it to room temperature to obtain a solution-treated tube blank; cold drawing is performed using a tube drawing machine, with a total deformation of 56~64% in multiple draws to obtain a cold-drawn tube blank; aging treatment is then performed, in which the cold-drawn tube blank is reheated to 600~650 ℃ and held at that temperature for 1~1.5 h. h, and then rapidly water-cooled to room temperature to obtain an aged tube blank; the prepared cobalt-chromium-based alloy matrix has an FCC structure, with tens of nanometer-sized manganese-rich precipitates inside the grains, which have an HCP structure; the tens of nanometer-sized manganese-rich HCP precipitates are distributed in twins and the matrix, coexisting with a large number of dislocations and nanotwins; the special structure of the coupling of nanotwins, dislocations, and nanoprecipitates gives the alloy extremely high strength; the tensile strength of the aged tube blank is higher than 1900 MPa and the hardness is higher than 670 HV.
2. The method for preparing a high-strength cobalt-chromium-based alloy for puncture needles as described in claim 1, characterized in that: Includes the following steps: (1) Raw material preparation: Prepare Co, Cr, Fe, Ni, Mo, Mn and Si raw materials according to the required proportions; (2) Vacuum induction melting: After weighing the raw materials, they are placed in an Al2O3 crucible and melted using an induction melting furnace; before melting, the vacuum degree is raised to 1.33×10 -4 ~ 1.33×10 -3 Pa, maintain for 2~2.5h; after turning off the vacuum pump, fill with 0.04 MPa high-purity argon gas as a protective atmosphere; then use a high-frequency induction coil to slowly heat to 1600~1650 ℃; after the block melts, pour it into a casting mold to obtain the casting billet; (3) Homogenization treatment: The casting billet is loaded into a vacuum heating furnace, heated to 1420~1460 ℃, and kept at the temperature for 12~24h to obtain a homogenized billet; (4) Hot extrusion: The homogenized billet is used to prepare tube blanks using a hot extrusion press; the temperature is heated to 1060~1180℃ before hot extrusion; the hot extrusion ratio is 8~20; hot extruded tube blanks are obtained after hot extrusion. (5) Solution treatment: The hot extruded tube blank is loaded into a heat treatment furnace and heated to 1100~1160℃ under vacuum or argon protection, held for 1~1.5h, and then rapidly water-cooled to room temperature to obtain the tube blank after solution treatment. (6) Cold drawing forming: The tube drawing machine is used for cold drawing forming. The total deformation of multiple drawing passes is 56~64% to obtain a cold drawn tube blank. When the size of the cold drawn tube blank is larger than the size of the puncture needle, steps (5) and (6) can be repeated until the size of the cold drawn tube blank meets the size requirements of the puncture needle to obtain the cold drawn tube of the puncture needle. (7) Aging treatment: The puncture needle is cold-drawn and then heated to 600~650 ℃ and kept at that temperature for 1~1.5 h. Then it is quickly cooled to room temperature to obtain the puncture needle tube after aging treatment. The puncture needle can be prepared by subsequent machining and polishing.
Citation Information
Patent Citations
Preparation method of cold-processed cobalt-based alloy rod wire
CN111485138A
Method of making cobalt-based alloy tubes having enhanced mechanical performance characteristics and a tube formed by the method
US20080215017A1